Trabalho de docência e comportamento micro-organizacional: A motivação do docente na área da saúde - Molina, Vera Lúcia Ignácio [UNESP]; Kamimura, Quésia P. (My University, 2009)
Using the motivograma and interviews the degree of motivation of the survey participants was defined as satisfactory. On one hand there is satisfaction with the physiological needs, self-esteem and self confidence, on the other there is high dissatisfaction with the association and self-realization, justifying the request for strengthening the membership and performance improvements in the research area. Linking up security and association with the other ones group protection sentiments and work environment dependence sentiments prevail. It was concluded that: (1) Those satisfied ones declare that they are safe, protected and with good self-esteem doing their teaching work. The ones dissatisfied with the non-group belonging demonstrate dissatisfaction with the self-realization and expose their difficulties with social ties and the lack of integration in the teaching work. (3) The degree of motivation satisfactory is related to the satisfaction of basic needs, located in the first steps of Maslow's hierarchy. Accepting that the changes in higher education require motivated behaviors, the question arises: how can the motivation in teaching work be possible if the majority of organizations do not find a way to deal with the person of the Professor? Finally, the context of work is predominant in the provision of job satisfaction in teaching.
Docent work and micro-organizational behavior: The motivation of the docent in the field of health
Keywords: Organization of education; Organization of health; Organizational behavior; Teaching; Work of teaching